1991
DOI: 10.1128/jvi.65.8.4198-4203.1991
|View full text |Cite
|
Sign up to set email alerts
|

Antigenicity of rabies virus glycoprotein

Abstract: Although the number of antigenic sites on the rabies virus glycoprotein that have been described regularly increases with time, no attempt has been made to carefully evaluate the relative importance of each of these sites. Here we provide a more precise description of the antigenicity of the protein in mice of the H-2d haplotype; we developed this description by using 264 newly isolated monoclonal antibodies (MAbs) and a collection of neutralization-resistant (MAR) mutants. Most of the MAbs (97%) recognized an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
89
1
9

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(101 citation statements)
references
References 26 publications
2
89
1
9
Order By: Relevance
“…Furthermore, a nucleotide transversion (T3G), believed to be less frequent than transition events, was independently found twice. The number (4) of srr mutations was similar to the number of mutants selected for their resistance to the neutralization by a single MAb (6,28,43,49) (Fig. 7).…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…Furthermore, a nucleotide transversion (T3G), believed to be less frequent than transition events, was independently found twice. The number (4) of srr mutations was similar to the number of mutants selected for their resistance to the neutralization by a single MAb (6,28,43,49) (Fig. 7).…”
Section: Discussionsupporting
confidence: 54%
“…The abscissa shows the number of different amino acid substitutions found at each amino acid position. Most of the mutations have already been described previously (6,28,43,44,49,59), with the exception of the mutations at positions 203, 210 in site II, 331 in site III, and 342 and 354 in minor site a (F. Lafay It is noteworthy that the K330NÏ©R333M mutant, resulting from two independent mutational events (12), could not have been selected on CVS stocks in this selection process. The role of p75NTR in RV infection is still unknown, and some previous reports need to be reevaluated in the light of recent data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Monoclonal antibodies (mAbs) have been very useful tool for studying the relationships between the molecular structures and functions of proteins. Using many mAbs, epitopes of the rabies virus G protein have been studied for years, and at least three major antigenic sites (I, II and III) have been identified on the ectodomain of the G protein (3,6,15). One of the major epitopes studied so far is the highly conserved antigenic site III which is recognized by a virus-neutralizing mAb #194-2, and extensive studies with the escape mutants demonstrated that an amino acid substitution in the epitope site (e.g., Arg-333 to Gln) affected the neurovirulent nature of the virus (5,26).…”
mentioning
confidence: 99%